The voices of incarcerated women at the forefront of parenting program development: a trauma-informed approach to education - Belinda J. Lovell; Mary P. Steen; Angela E. Brown; Adrian J. Esterman (Health & Justice, 2022)
Abstract Background The lives of women experiencing incarceration are complex, impacting many aspects of parenting. Incarceration can present an opportunity for women to access parenting education. However, their specific needs have to be considered. Few parenting programs for women experiencing incarceration have involved the women as part of their development. Methods Six focus groups were conducted in a prison setting involving thirty-one women to explore and understand their parenting education needs. Results Four main themes were identified to reflect the complex lives of the women and their parenting education needs. These themes were: working towards a positive self, communication as a lifeline, supporting and nurturing their children and hopefulness and reconnecting. The trauma women experienced in their lives was apparent during discussions. Conclusion Women requested a non-judgmental parenting program to be developed to meet their specific needs and circumstances. The program needed to be designed to enable them to share stories with women in similar situations. Women gave insights into some of the specific content and topics they would like included in a parenting program. The women revealed experiences of trauma in their lives, demonstrating the importance of the need for a trauma informed approach to parenting education.